Understanding compassion fatigue among social workers: a scoping review - Tian Wu; Chun-Rong Lu (Frontiers in Psychology)
Exposure to significant sources of trauma and stress among social workers is increasingly identified as an important issue that can impact the quality of professional services, and the social worker’s well-being. There is more and more literature focusing on this phenomenon and related concepts. However, to our knowledge, there has been no published systematic review of the literature on compassion fatigue (CF) among social workers. Therefore, we performed a systematic scoping review by searching five electronic databases for studies published from 2001 to 2021, with the aim of identifying relevant literature. A total of twenty-nine studies were selected in the review following the systematic search strategy. Five themes were identified through the use of a narrative approach to synthesizing the literature by a Five-step framework of scoping review, including the prevalence, factors related, attributes and characteristics, consequences and strategies or interventions to reduce compassion fatigue among social workers. Findings revealed that few studies had examined the consequences and tested the effectiveness of specific interventions. Furthermore, future research involving concept analysis and related theoretical model was required in the field of social work.